Significance of glycolytic metabolism-related protein expression in colorectal cancer, lymph node and hepatic metastasis. Issue 1 (December 2016) - Martins, Sandra; Amorim, Ricardo; Viana-Pereira, Marta; Pinheiro, Céline; Costa, Ricardo; Silva, Patrícia; Couto, Carla; Alves, Sara; Fernandes, Sara; Vilaça, Sónia; Falcão, Joaquim; Marques, Herlander; et al.
Abstract Background Colorectal cancer (CRC) is one of the most common malignancies and a leading cause of cancer death worldwide. Most cancer cells display high rates of glycolysis with production of lactic acid, which is then exported to the microenvironment by monocarboxylate transporters (MCTs). The main aim of this study was to evaluate the significance of MCT expression in a comprehensive series of primary CRC cases, lymph node and hepatic metastasis. Methods Expressions of MCT1, MCT4, CD147 and GLUT1 were studied in human samples of CRC, lymph node and hepatic metastasis, by immunohistochemistry. Results All proteins were overexpressed in primary CRC, lymph node and hepatic metastasis, when compared with non-neoplastic tissue, with exception of MCT1 in lymph node and hepatic metastasis. MCT1 and MCT4 expressions were associated with CD147 and GLUT1 in primary CRC. These markers were associated with clinical pathological features, reflecting the putative role of these metabolism-related proteins in the CRC setting. Conclusion These findings provide additional evidence for the pivotal role of MCTs in CRC maintenance and progression, and support the use of MCTs as biomarkers and potential therapeutic targets in primary and metastatic CRC.